Bank Wakaf: Solusi Pemberdayaan Sosial Ekonomi Indonesia - Fahmi Medias (Indonesian Journal of Islamic Literature and Muslim Society, 2017)
This article attempts to identify the strategic role of cash waqf as an alternative financial instrument in the economic development of Indonesia in the field of social, religious, educational, and health, as well as to identify the problems faced by the social institution that has existed in Indonesia in the management of cash waqf. After the economic crisis hit Indonesia in 1998, the existence of cash waqf becomes very strategic and is deemed appropriate to give the mutual fund model that very potential in real sector to empower and strengthen the social economy Indonesia. However, cash waqf as one of the most potential sources of funds which have not been used optimally in Indonesia. This is due to a large number of waqfs are managed in a traditional consumer. On the other hand, Islamic finance institutions which manage the Waqf money haven't been able to manifest cash waqf benefits for socio-economic empowerment. At the end of the discussion, this article emphasizes the importance of the cash waqf funds mobilization of society through the creation of waqf bank to expand the potential of cash waqf in improving the social and economic welfare of society in Indonesia.